Pemetaan dan Perencanaan Tempat Pemakaman (Studi Kasus: Tempat Pemakaman Kerukunan Keluarga Wuamesu Ende Makassar) - Richard Frans; Hendry Tanoto Kalangi (G-Tech: Jurnal Teknologi Terapan, 2024)
Kerukunan Keluarga Wuamesu Ende Makassar is a social organization situated in the city of Makassar. One of the initiatives undertaken by this group is to establish burial sites for its members and make them accessible to other Ende communities residing in the Makassar City area, Gowa Regency, and other regions. However, the given burial grounds currently lack a well-defined topological map. Hence, the mapping process was conducted to determine the topological characteristics and dimensions of the TPBU. The total station instrument is employed to ascertain the dimensions of the site and the altitude of the TPBU. In addition to mapping, a prototype tomb design was developed as a potential option, particularly for individuals of the Christian faith. The mapping results indicate that the size of the TPBU is approximately 5,000 square meters, with a width of 49.38 meters and a length of 117.56 meters. The TPBU has the capacity to accommodate 390 graves in this region.